2004
DOI: 10.1124/dmd.32.5.536
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Hepatic and Extrahepatic Enantioselective Sulfoxidation of Albendazole and Fenbendazole in Sheep and Cattle

Abstract: ABSTRACT:The enantioselective sulfoxidation of the prochiral anthelmintic compounds albendazole (ABZ) and fenbendazole (FBZ) was investigated in liver, lung and small intestinal microsomes obtained from healthy sheep and cattle. The microsomal fractions were incubated with a 40 M concentration of either ABZ or FBZ. Inhibition of the flavin-containing monooxygenase (FMO) system was carried out by preincubation with 100 M methimazole (MTZ) either with or without heat pretreatment (2 min at 50°C). ABZ and FBZ wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 44 publications
4
71
2
Order By: Relevance
“…It was reported that the major monooxygenases that catalyze the formation of aliphatic sulfoxides are the P450s and FMOs (16)(17)(18)(19)(20)(21). Identification of the human P450 and FMO enzymes Remaining activity % is metabolic activity in the presence of inhibitor divided by metabolic activity in microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the major monooxygenases that catalyze the formation of aliphatic sulfoxides are the P450s and FMOs (16)(17)(18)(19)(20)(21). Identification of the human P450 and FMO enzymes Remaining activity % is metabolic activity in the presence of inhibitor divided by metabolic activity in microsomes.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, antibodies directed toward FMOs typically inhibit catalytic activity weakly, if at all, and the only chemical inhibitors are competitive substrates. The most commonly used alternative substrate to inhibit FMO in vitro (Mani et al, 1993;Narimatsu et al, 1999;Rawden et al, 2000;Pike et al, 2001;Attar et al, 2003;Wynalda et al, 2003;Virkel et al, 2004) and in vivo (Ruse & Waring, 1991;Nace et al, 1997;Wang et al, 2000) has been methimazole (see next section for further discussion of methimazole). FMO activity is unaffected by non-ionic detergent or carbon monoxide, but most FMOs are readily inhibited by short incubations at temperatures of 45-50 °C.…”
Section: Role Of Flavin-containing Monooxygenase In Drug Metabolismmentioning
confidence: 99%
“…FMO readily S-oxygenates simple sulfides such as methyl-, ethyl-, ethyl methyl, 4-chlorophenyl methyl, and diphenyl sulfides Nnane & Damani, 2003a. Sulfide-containing drugs, for which FMO is active in S-oxygenation to sulfoxides, include cimetidine, rantidine, thioridazine, 7-(1,3-thiazolidin-2-methyl) theophylline, (+)-cis-3,5-dimethyl-2-(3-pyridyl)-thiazolidin-4-one, sulindac sulfide, clindamycin, albendazole, and fenbendazole (Eriksson & Bostrom, 1988;Grosa et al, 1992;Cashman et al, 1993b;Lanusse et al, 1993;Moroni et al, 1995a;Nunoya et al, 1995;Hamman et al, 2000;Rawden et al, 2000;Nnane & Damani, 2003aWynalda et al, 2003;Virkel et al, 2004). Although not employed as a therapeutic drug, the cyclic sulfide tetrahydrothiophene is the best substrate to date, as evidenced by submicromolar K m values, found by us with FMO.…”
Section: Role Of Flavin-containing Monooxygenase In Metabolism Of S-cmentioning
confidence: 99%
“…Their metabolic patterns and the resultant pharmacokinetic behaviors are relevant in the attainment of high and sustained concentrations of pharmacologically active drugs/metabolites at the target parasite (8). Evidence from microsomal investigations in a number of species suggests that CYP3A4 and flavin-containing monooxygenase (FMO) are major enzymes responsible for the formation of sulfoxide metabolites from albendazole (4,9,10) and fenbendazole (4,5) (Fig. 1).…”
mentioning
confidence: 99%
“…Benzimidazole anthelmintics are extensively metabolized in domestic animals and humans. Animal and microsomal incubation studies have demonstrated rapid conversion of albendazole and fenbendazole to a sulfoxide metabolite and subsequently a sulfone metabolite (2)(3)(4)(5)(6). Sulfoxide metabolites are responsible for the systemic biological activity of benzimidazole drugs (7).…”
mentioning
confidence: 99%